2016
DOI: 10.1080/09205063.2016.1239945
|View full text |Cite
|
Sign up to set email alerts
|

Poly(butylene adipate-co-terephthalate) scaffolds: processing, structural characteristics and cellular responses

Abstract: The aliphatic-aromatic copolyester, poly(butylene adipate-co-terephthalate) (PBAT) combines good mechanical and thermal properties with biodegradation ability. However, until now, researches in its potential medical use remain limited. Only in a few studies blends of PBAT with routinely used biocompatible polymers had been prepared and investigated regarding tissue engineering applications. Therefore, in this study, we decided to determine processability of neat PBAT as a scaffold material for bone tissue by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Two-dimensional PBAT matrices were also fabricated by traditional electrospinning for comparison based on our previous study [25]. PBAT was first dissolved in HFIP at a concentration of 24% (w/v) and transferred into a syringe with a 21-gauge needle.…”
Section: Preparation Of 2 D Pbat Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two-dimensional PBAT matrices were also fabricated by traditional electrospinning for comparison based on our previous study [25]. PBAT was first dissolved in HFIP at a concentration of 24% (w/v) and transferred into a syringe with a 21-gauge needle.…”
Section: Preparation Of 2 D Pbat Matricesmentioning
confidence: 99%
“…Characteristics of PBAT, HAp-PBAT and B-HAp-PBAT fibrous matrices are given in Table 2. In order to make a comparison between 2 D and 3 D fibrous matrices, characteristics of 2 D PBAT fibrous matrices fabricated in our previous study [25] are also presented in Table 2. As seen from this table, porosity of the 2 D fibrous matrices is $86% whereas that of 3 D fibrous matrices is $91%.…”
Section: Morphological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The water contact angles of PLA and PCL electrospun membranes prepared in this work are also very different from those of the corresponding nonporous films obtained by hot‐pressing (111.8° vs 84.2° and 135.7° vs 67.3°). It has also been reported that the water uptake capacity of a material is closely related to its porosity and increases when the porosity increases …”
Section: Resultsmentioning
confidence: 99%
“…PBAT is biodegradable by microorganisms and has an adjustable balance between optimal biodegradation and desirable physical-chemicalproperties (15). Thus, the use of PBAT, alone or in composite form, represents a great promise for the tissue engineering, since it presents desirable degradation rate, good thermal and mechanical properties and easy processability (16).…”
Section: Introductionmentioning
confidence: 99%